Functional mapping of the A2 domain from human factor VIII - Plantier, Jean-Luc; Saboulard, Didier; Pellequer, Jean-Luc; Négrier, Claude; Delcourt, Marc (Thrombosis and Haemostasis, 2012)
Coagulation factor VIII (FVIII) is a multidomain glycoprotein in which the FVIII A2 domain is a key structural element. We aimed at identifying residues within FVIII A2 domain that are crucial for the maintenance of the cofactor function. A high number (n=206) of mutants were generated by substituting original residues with alanine. The mutants were expressed in COS-1 cells and their antigen levels and procoagulant activities were measured. The residues were classified in three categories: those with a non-detrimental alteration of their activities (activity >50 % of control FVIII; n=98), those with a moderate alteration (15 %<activity<50%; n=45) and those that were severely affected (activity<15%; n=63). The mutants sensitive to mutation were retrieved in the HAMSTeRS database with a higher percentage than those that were not affected (58.8% vs. 9.2%). The results revealed the existence of clusters of residues that are sensitive (Arg418-Phe436, Thr459-Ile475, Ser535-Gly549, Asn618-Ala635) or not (Leu398-Arg418, Pro485-Asp500, Gly506-Gly520, Pro596-Asp605) to mutations. The stretches of residues sensitive to mutations were buried within the molecule suggesting that these amino acids participate in the maintenance of the A2 domain structure. In contrast, residues resistant to mutations formed external loops without well- defined structures suggesting that these loops were not crucial for the process of factor X activation. This study provided a detailed map of the FVIII A2 domain between residues 371 and 649, identifying residues crucial for maintaining FVIII function and residues that can be mutated without jeopardising the coagulant activity.
Keywords: Coagulation factors; factor VIII; protein structure / folding; protein function / activity